Study on Utilizing Oil Palm Empty Fruit Bunch Waste into Carbon Nanodots - Anindita, Faradisa; Naani, La; Permana, Dian; Kedang, Yohana Ivana; Karelius, Karelius (Journal of The Indonesian Society of Integrated Chemistry, 2024)
This investigation introduces a proficient synthesis of carbon nanodots (CND) utilizing empty fruit bunches (EFB) as an environmentally friendly and economical carbon precursor. The synthesis method involves a combination of pyrolysis and hydrothermal. The optical and physicochemical properties of CND were investigated through X-ray diffraction (XRD), Fourier Transform Infrared (FTIR), Transmission Electron Microscopy (TEM), Particle Size Analysis (PSA), UV-visible, and fluorescence spectroscopy. The CND exhibit a spherical morphology, as confirmed through TEM imaging, with an amorphous structure. Size distribution analysis reveals a predominant particle size range between 3.8 and 4.8 nm, and an average diameter of 4.5 nm. Additionally, these CND demonstrated excellent aqueous dispersibility and exhibited fluorescence emission dependent on excitation. The synthesis procedure utilized a simple method, efficiently converting waste materials into valuable end products.